Determination of epigenetic age through DNA methylation of NPTX2 gene using buccal scrapes: A pilot study - Nawal Khan; Radhika Bavle; Soumya Makarla; Paremala Konda; S Amulya; Sreenitha Hosthor (Journal of Forensic Dental Sciences, 2019)
Context: DNA methylation (DNAm) age can be used to evaluate the chronological age of individuals often called “epigenetic age.” In this study, buccal scrape samples were used for the determination of epigenetic age. Aims: To examine if epigenetic age could be determined using neuronal pentraxin 2 (NPTX2) gene in buccal cells. Setting and Design: This cohort study was designed to validate the use of buccal cells for epigenetic age estimation. Sanger sequencing was used to determine the genetic sequence of the gene of interest postamplification. Nucleotide base sequence for NPTX2 gene was obtained for each case using this protocol. Subjects and Methods: The study was conducted on buccal scrapes obtained from 26 subjects of both genders, whose age varied from 1 to 65 years. The samples, collected by wooden spatulas, were placed in cell suspension buffer and stored at 4°C until transported to the laboratory. Results: Methylation levels of 5’-C-phosphate-G-3’ located in the gene NPTX2 of 26 subjects were studied and analyzed by bisulfate sequencing. The percentage of methylation in this study falls in the range between 15% and 51%. Conclusion: In this study, a sufficient amount of gDNA was retrieved from the buccal cells, thus confirming that buccal scrape was a feasible technique to obtain ample DNA. This study also showed that DNAm-polymerase chain reaction method was a feasible method for the evaluation of methylation pattern of NPTX2 gene.